IS SOCIETY WILLING TO DONATE TO WAQF? OPINIONS OF THE STATE ISLAMIC RELIGIOUS COUNCILS IN MALAYSIA - Mohamad Suhaimi, Farhana; Ab Rahman, Asmak (Jurnal Syariah, 2017)
This study aims to identify the awareness and understanding of Muslims in Malaysia regarding the development of waqf property. This research was conducted through interviews with selected State Islamic Religious Councils (MAINs) Waqf Department officers as they have vast experience in leading society towards waqf property management. In addition, a literature review was undertaken on contemporary studies dealing with this subject. The study found that awareness and understanding of Muslims regarding waqf property in Malaysia varies due to different approaches instituted by MAINs in their respective states.